Global politics in the human interest - Gurtov, Mel (New Delhi, 2010)
Traditional studies of world politics emphasize the struggle between states as they search for national security. But increasing interdependence has transformed the world political agenda, creating the need for new tools to explain the changing reality of global politics . Global Politics in the Human Interest provides those tools. This fully revised fifth edition thoroughly covers post- September 11 developments. Addressing such interrelated issues as terrorism, democratic transitions, nationalism, human rights violations, armed conflicts, economic globalization, and sustainable development, Gurtov explores the threats and opportunities posed by the changing world order. The book retains its practical bent, revealing how global politics affects the quality and content of people's lives. Contents: Crisis and interdependence in contemporary world politics: Global insecurity ??? A brief report on the state of the planet ??? From interdependence to globalization ??? Trend line 1: The new structure of world affairs ??? Trend line 2: Democratization's rise and fall ??? Case study 1: 9/11 and the war on terror ??? Realism and corporate globalism in theory and practice: The realist perspective ??? Corporate globalism and the world economy ??? Rivals or partners ??? Case study 1: Postwar planning for the "American Century," ??? Case study 2: Capitalist dominoes ??? The Mexican and Asian financial crises ??? Case study 3: Another American century? The invesion of Iraq ??? World politics in global-humanist perspective: The search for a third way ??? Values, methods measurements objectives ??? Case study 1: The US-Soviet arms race during the cold war ??? Case study 2: North Korea Iran, and weapons of mass destruction ??? The third world and the fourth: Human rights, environmental decline, and underdevelopment: Defining the "Third World," ??? A Third World country profile ??? Case studies of crisis and renewal ??? The United States and China: Cooperation or conflict? : Alone
Keywords: World politics